2020
DOI: 10.37398/jsr.2020.640122
|View full text |Cite
|
Sign up to set email alerts
|

Nickel and Arsenite Responsive Proteomic Alterations in Cyanobacterium Anabaena PCC7120

Abstract: Ecological adaptation of organisms to environmental stresses including heavy metals denotes a novel example of evolution under extreme selection pressure. Cyanobacteria represent the largest and most diverse group of prokaryotes, capable of performing oxygenic photosynthesis and are frequently found in environments contaminated with heavy metals. Quite a lot of proteomic studies have investigated the effects of metals such as Cu, Co, Cd, and As(V) etc. on diazotrophic cyanobacteria. However, proteomic studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…Nickel has been found to be more toxic in cyanobacteria causing distorted growth, pigment deterioration and arresting the excitation energy transfer in phycobilisomes in Nostoc muscorum [ 9 ]. Recently, Prajapati et al [ 10 ] have reported down regulation of several proteins along with of carbon metabolism and photosynthesis in Ni stressed Anabaena PCC 7120. The excess generation/accumulation of reactive oxygen species (ROS) causes damage to cellular membranes (lipids and proteins), enzymatic activities, reserve food (carbohydrates), genetic material (DNA) etc.…”
Section: Introductionmentioning
confidence: 99%
“…Nickel has been found to be more toxic in cyanobacteria causing distorted growth, pigment deterioration and arresting the excitation energy transfer in phycobilisomes in Nostoc muscorum [ 9 ]. Recently, Prajapati et al [ 10 ] have reported down regulation of several proteins along with of carbon metabolism and photosynthesis in Ni stressed Anabaena PCC 7120. The excess generation/accumulation of reactive oxygen species (ROS) causes damage to cellular membranes (lipids and proteins), enzymatic activities, reserve food (carbohydrates), genetic material (DNA) etc.…”
Section: Introductionmentioning
confidence: 99%